Impact of Climate Change in Nigerian Wetland Ecosystems on Plant Genetic Resources - Anthony O. Ukpene; Collins O. Molua (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
The research focused on particular character traits of some plants in the ecosystems of Nigeria's wetlands. The idea was to highlight the plants' adaptive mechanisms and conservation requirements in response to the vagaries of climate change. The field data collection covered 10 wetland sites spread across the Niger Delta, Nigeria, selected to represent a diversity of plant morphology, biological chemistry, and population structure parameters. The investigated morphological elements in leaves, flowers, and fruit showed considerable variation in their size, shape, and color among species. The biochemical data derived from isozyme profiles in turn gave rise to a higher degree of genetic variation, which was further demonstrated through population structure data that revealed selective pressures on the mating success of the population and the demography of individuals. The environmental conditions, such as pH level, temperature, oxygen, and nitrogen levels, along with others, determined the variety of habitats in the cattail marsh at every site. These data provide evidence-based insights related to wetland ecology and plant genetics as the basis for a deeper understanding and prioritizing the conservation of these very special ecosystems against the background of climate change challenges. Areas of future research that should be considered include more investigations about genetic heterogeneity, the role of ecological interactions, and the integration of management strategies for reforming wetlands conservation. This investigation comprehensively explained wetland ecosystems and emphasized the imperative for immediate conservation measures in order to guarantee ecological integrity and the diversity of life in wetland ecosystems.